Developing ecolabels to encourage sustainable eating in restaurants: A randomized experiment - Cristina J. Y. Lee; Joshua Petimar; Amanda B. Zeitlin; Caroline Collis; Lauren Cleveland; Aviva A. Musicus; Anna H. Grummon (PLoS ONE, 2025)
Restaurants are increasingly adopting ecolabels to highlight environmentally friendly menu offerings. However, it remains unclear which ecolabel design is the most effective at encouraging consumers to select these items. This study aimed to determine which of 4 common ecolabel formats are perceived as most effective at encouraging selection of environmentally sustainable foods. We conducted an online experiment with 2,169 US adults in August 2023. Participants were randomized to 1 of 5 label formats, including a control format (e.g., QR code) and 4 ecolabel formats: text-plus-icon, text-only, icon-only, or numeric ecolabels. Participants viewed 3 label variations of their randomly assigned label format. Participants rated each label variation on perceived effectiveness for encouraging environmentally sustainable food choices (primary outcome) and other label reactions (e.g., thinking about environmental impacts; secondary outcomes) on 5-point scales. All ecolabels were perceived as more effective at encouraging environmentally sustainable food choices than the control labels (range of average differential effects [ADEs]=.26 to .82, p s < .001). Among ecolabels, the text-plus-icon ecolabels were perceived as the most effective (mean = 3.17), followed by icon-only (mean = 2.95), text-only (mean = 2.93), and numeric (mean = 2.62) ecolabels. A relatively similar pattern emerged for secondary outcomes. Text-plus-icon ecolabels may be the most promising ecolabel format to encourage selection of sustainable foods. Restaurants, third-party certification systems, and policymakers interested in encouraging sustainable food choices in restaurants could consider adopting text-plus-icon ecolabels on restaurant menus, though further testing is needed to determine effects on behavior.